Village Tourism as a Key to Meet the Challenge of Sustaining Tourism in Goa - Kamat, Smitha Bhandare (Prabandhan: Indian Journal of Management, 2011)
On the historic day of 19th December 1961, Portuguese colonialism, extending to 451 long years, finally came to an end in Goa. Post Liberation, in the mid sixties, the hippies discovered the kingdom of good times in Goa, and for this particular horde of rebels, nothing seemed more enthralling. They progressively nestled at the far end of the 105 kms. white shoreline, fringed with swaying palms, the green fields and orchards. Commercialization of the virgin white beaches, with its irresistible sun and surf was yet to take place. But, for some strange reason the ’hippy image’ stuck for good, it probably had to do with, if not more, an equally fun loving and peace loving local populace. The historical past, and the strategic alliance with its heritage, not to forget its irresistible natural beauty, only served as powerful paraphernalia to attract the guests to its doorsteps. Over the decades, the tourist traffic to this state has registered a phenomenal growth, and is incessant. Given the fact, Goa has witnessed a reckless growth of tourism in the state, and the exclusive and excessive dependence on beach centric tourism warrants a need to inject sustainability by means of diversification. Is Village/ Rural tourism the answer is being examined in the present paper. A case of two villages of north Goa, namely Candolim and Assagao is taken up for analysis.